Perlindungan Hukum Hak Merek Bagi Pengembangan Pelaku Usaha Bidang Makanan Di Kota Semarang - Endang Setyowati; Ana Kadarningsih (Lembaga Pengembangan Kinerja Dosen, 2023)
MSMEs are one of the strengths in economic development in Semarang City, especially in the food sector. However, food MSMEs are the first rank that have not registered a brand. The current rise in imitation and counterfeiting of brands has made legal protection of brands an important requirement in business development. The problem in this research is how to legally protect brand rights for food MSMEs in Semarang City. This research aims to provide knowledge to food MSMEs about legal protection of brand rights so that food MSME businesses can develop with legal certainty. This research uses an empirical normative juridical approach and is descriptive analysis. The results of the research were that the Department of Cooperatives and Micro Enterprises of Semarang City provided free brand registration facilities for MSMEs that were only supported, and many problems were found related to the legal protection of brand rights in the City of Semarang..